Perception and reason - Brewer, Bill, Dr. (Oxford : Clarendon Press ; New York : Oxford University Press, 1999)
This volume presents an original view of the role of conscious experience in the acquisition of knowledge. It argues that experiences must provide reasons for beliefs if there are to be any beliefs about the mind-independent world at all.
8.1 Non-Demonstrative Perceptual Knowledge8.2 Russell's Principle of Acquaintance -- 8.3 Externalism and A Priori Knowledge -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W
Includes bibliographical references (pages 269-276) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Knowledge, Theory of; Perception (Philosophy); Experience; Théorie de la connaissance; Perception (Philosophie); Expérience.; epistemology; perception; PHILOSOPHY -- Epistemology; Experience; Knowledge, Theory of; Perception (Philosophy); Waarneming; Kennistheorie